Edtech Implementation at English Teachers Competencies Development Program (PKGBI) 2024 conducted by Kelas Kreatif Trainers - Kuraesin, Cicin; Khoirotusyarifah (UIN Sunan Gunung Djati Bandung, 2025)
English Teacher Competencies Development Program (PKGBI), a national initiative aimed at enhancing teacher competence, has adopted several digital tools to improve training delivery and participant engagement. This paper examines the integration of educational technology (Edtech) in the PKGBI 2024 program, facilitated by trainers from the Kelas Kreatif Personal Development Community. Through a case study approach, this paper explores how Edtech solutions were implemented by trainers to enrich the learning experiences of educators joined the program. Key technologies, including Learning Management Systems (LMS), application, platforms, and tools, are evaluated for their effectiveness in meeting training objectives. Findings indicate that Edtech implementation during synchronous and asynchronous sessions covers variations of Edtech namely Pearson English Portal (PEP), Google meet, Google drive, Wordwall, Canva, Quizizz, Wheel of names, Genially, Learning apps, Padlet, Bamboozle, Gslide, Microsoft Power Point, Mentimeter, Bookwidgets, Youtube, Edpuzzle, Nearpod, and Kahoot. Wordwall was found to be the most frequent used by trainers, while Genially is the least used by trainers. In Addition, Canva is the most recommended edtech to use in online setting classroom, specifically PKGBI classroom setting. It was found that Education technology implementation prominently requires practicality followed by interactivity and familiarity resulted in favorability. The paper concludes best practices for edTech implementation in large-scale teacher training programs and its potential to transform professional development in education.